Sport integrity opportunities in the time of coronavirus - Pitsiladis, Y.; Muniz-Pardos, B.; Miller, M.; Verroken, M. (Sports Medicine, 2020)
The coronavirus (COVID-19) pandemic provides a unique opportunity for reflection on integrity challenges facing sport. The imposed lockdown in response to this global crisis has resulted in most sporting events being postponed or cancelled including the 2020 Olympic Games. While this pandemic threatens to overwhelm an already fragile world sport, it provides an unprecedented opportunity for stakeholders in sport to learn vital lessons from COVID-19, to delve into unresolved integrity issues and develop creative and long-lasting solutions. This commentary focuses on two issues affecting the integrity of sport: doping and technological fairness.